Protection of the Extracts of Lentinus edodes Mycelia against Carbon-Tetrachloride-Induced Hepatic Injury in Rats. (22nd May 2012) - Chen, Mei-Fen; Chung, Hsien-Hui; Lu, Han-Lin
Abstract : Lentinus edodes is the medicinal macrofungus showing potential for therapeutic applications in infectious disorders including hepatitis. In an attempt to develop the agent for handling hepatic injury, we used the extracts of Lentinus edodes mycelia (LEM) to screen the effect on hepatic injury in rats induced by carbon tetrachloride (CCl4 ). Intraperitoneal administration of CCl4 not only increased plasma glutamic oxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) but also decreased hepatic superoxide dismutase (SOD) and glutathione peroxidase (GPx) levels in rats. Similar to the positive control silymarin, oral administration (three times daily) of this product (LEM) for 8 weeks significantly reduced plasma GOT and GPT. Also, the activities of antioxidant enzymes of SOD and GPx were elevated by LEM. in liver from CCl4 -treated rats, indicating that mycelium can increase antioxidant-like activity. Moreover, the hepatic mRNA and protein levels of SOD and GPx were both markedly raised by LEM. The obtained results suggest that oral administration of the extracts of Lentinus edodes mycelia (LEM) has the protective effect against CCl4 -induced hepatic injury in rats, mainly due to an increase in antioxidant-like action.